Organska kemija: Urejeni zapiski predavanj - Kristl, Janja (University of Maribor Press, 2017)
Organic Chemistry: Edited Lecture Notes. Organic chemistry is the chemistry of carbon compounds. It deals with the structure, synthesis and properties of organic compounds. Organic compounds include: carbohydrates, proteins, enzymes, hormones, oil, gas, coal and many synthetic compounds (pigments, plastic materials, textile fibers etc.). Organic compounds can be found all around us (food, spices, fragrances, medicines, detergents, textile, polymers, organic fertilizers, agents for plant protection, growth stimulators…) and within all living organisms. These edited notes of lectures are intended to help students of agronomy study organic chemistry. Most of the textbooks covering the area of organic chemistry are mainly meant for students of chemistry. That kind of literature is mostly to comprehensive and difficult to understand for students of agronomy. In the notes, groups of organic compounds are comprehensively presented. The main activity of agriculture is the production of fodder and food, so the main emphasis of the notes is on organic compounds, which are the main constituents of fodder and food. The notes are divided into eleven chapters. The IUPAC nomenclature is included in every chapter and illustrated with basic examples. The most important reactions of compounds are included. Only those kinds of isomerism which have an important role in biological systems are included.